Use of 3-aminotriazole to isolate oleate/acetate non-utilizing mutants of Aspergillus nidulans - J. Ramon De Lucas; Susana Valenciano; Cristina Amor; Fernando Laborda (Fungal Genetics Reports, 1996)
Oleate non-utilizing (olu) mutants of Aspergillus nidulans were isolated on selective medium containing the catalase inhibitor, 3-aminotriazole (3-AT); in an attempt to obtain strains that would enable analysis of peroxisome biogenesis and function in filamentous fungi. Out of 816 putative mutants recovered from the selective medium, 40 were olu mutants. All of the olu mutants were unable to utilize acetate for growth, and so ressembled the acu mutants obtained by previous workers. The 40 olu mutants were placed in 5 different complementation groups.